The Effect of Face-to-face Sex Education on the Sexual Function of Adolescent Female Afghan Immigrants - Razia Hakimi; Masoomeh Kheirkhah; Jamileh Abolghasemi; Masumah Hakimi (Iran University of Medical Sciences, 2019)
Background: Access to precise information about sexual behaviors is an essential need for a favorable marital life. In the context of Afghan society culture, unawareness about sex issues in offspring on the verge of marriage could lead to an undesirable sexual function. The present study aimed to determine the effect of face-to-face sex education on the sexual function of adolescent female Afghan immigrants. Methods: This was a quasi-experimental study with a Pre-test-Post-test and a control group design. This research was conducted in the immigrant neighborhoods of Mashhad City, east of Iran, in 2018. Two charity centers with the largest numbers of Afghan immigrants were randomly selected as the case and control centers. A continuous sampling technique was applied to select the study participants. Besides, women who met the study inclusion criteria completed a demographic questionnaire and the Female Sexual Function Index (FSFI) before and at 4 and 8 weeks after the intervention. In addition to the center's routine programs, the experimental group received face-to-face education through PowerPoint slides, while the control group only received routine training of the center. The collected data were analyzed by SPSS using descriptive and inferential statistics. Results: There was no significant difference in the sexual function scores between the two study groups before the intervention (P=0.850), while there was a significant difference between them after 4 (P=0.003) and 8 weeks (P<0.001) of intervention provision. Conclusion: Face-to-face sexual training improved sexual function in adolescent female Afghan migrants; therefore, this training method could be used for sexual education in young female immigrants.